Associations of Blood Pressure and Heart Rate and Their Contribution to the Development of Cardiovascular Complications and All-Cause Mortality in the Russian Population of 25-64 Years - S. A. Shalnova; V. A. Kutsenko; A. V. Kapustina; E. B. Yarovaya; Yu. A. Balanova; S. E. Evstifeeva; A. E. Imaeva; S. A. Maksimov; G. A. Muromtseva; N. V. Kulakova; O. N. Kalachikova; T. M. Chernykh; et al. (Столичная издательская компания, 2020)
Aim. To study the relationship of blood pressure (BP) and heart rate (HR) in a sample of men and women 25-64 years old and their predictive value for the development of fatal and non-fatal cardiovascular diseases (CVD) and mortality from all causes.Material and methods. Prospective observation was for cohorts of the population aged 25-64 years from 11 regions of the Russian Federation. 18,251 people were included in the analysis. Each participant gave written informed consent. All surveyed persons were interviewed with a standard questionnaire. BP was measured on the right hand with an automatic tonometer. BP and HR were measured twice with an interval of 2-3 min with the calculation of the average value. The patients were divided into 4 groups: the first group with BP<140/90 ><140/90 mm Hg and HR≤80 beats/min; the second group - BP<140/><140/90 mm Hg and HR>80; the third group - BP≥140/90 mm Hg and HR≤80; the fourth group - BP≥140/90 mm Hg and HR>80 beats/min. Risk factors and cardiovascular history were analyzed as well. Deaths over 6 years of follow-up occurred in 393 people (141 - from CVD). Statistical analysis was performed using the open source R3.6.1 system.Results. A HR>80 beats/min was found in 26.3% of people with BP≥140/90 mm Hg, regardless of medication. Analysis of the associations between HR and BP showed that for every increase in HR by 10 beats/min, systolic BP increases by 3 mm Hg. (p<0.0001). The group with HR>80 beats/min and BP≥140/90 mm Hg had the shortest life expectancy (p<0.001). Adding an increased HR to BP≥140/90 mm Hg significantly><0.001). Adding an increased HR to BP≥140/90 mm Hg significantly worsened the prognosis of patients. Similar results were obtained in the analysis of cardiovascular survival. Elevated BP and elevated HR had the same effect on outcomes, except for the combined endpoint, where the contribution of elevated BP was predominant. However, their combined effect was the largest and highly significant for the development of the studied outcomes, even after adjusting for other predictors. With an increase in HR by every 10 beats/min, the risk of mortality increased statistically significantly by 22%.Conclusion. The prevalence of HR>80 beats/min in people with BP≥140 mm Hg amounted to 26.34%. Every 10 beats/min significantly increases the risk of mortality by 22%. Increased HR with elevated BP leads to increased adverse outcomes.